2008
DOI: 10.1080/08927020802036005
|View full text |Cite
|
Sign up to set email alerts
|

Microcapsules for controlled release fabricated via layer-by-layer self-assembly of polyelectrolytes

Abstract: Layer-by-layer (LbL) self-assembly of oppositely charged polyelectrolytes on different templates by alternating deposition is a versatile method enabling the construction of ultrathin multilayer films with tunable thickness, composition, and functions. The principal driving force for the LbL self-assembly is dominantly the electrostatic attraction between the polyelectrolyte components accompanied with other associative interactions, such as hydrogen-bonding, hydrophobic interaction, charge-transfer and so on.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The capsules templated on the CaCO 3 cores have been successfully applied for various biomedical applications including intracellular and extracellular drug delivery [ 14 , 15 ] and medical diagnostics [ 16 ]. A number of recent works on CaCO 3 templated capsules is devoted to the investigation of drug release performance of the capsules [ 17 , 18 , 19 , 20 , 21 ]. Different release behavior for the capsules of identical composition but templated on the cores of different nature (MnCO 3 and melamine formaldehyde) revealed that the capsules prepared using different core materials can be either hollow or filled with an internal polymer matrix present into the capsule lumen [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The capsules templated on the CaCO 3 cores have been successfully applied for various biomedical applications including intracellular and extracellular drug delivery [ 14 , 15 ] and medical diagnostics [ 16 ]. A number of recent works on CaCO 3 templated capsules is devoted to the investigation of drug release performance of the capsules [ 17 , 18 , 19 , 20 , 21 ]. Different release behavior for the capsules of identical composition but templated on the cores of different nature (MnCO 3 and melamine formaldehyde) revealed that the capsules prepared using different core materials can be either hollow or filled with an internal polymer matrix present into the capsule lumen [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LBL multilayers have been used to encapsulate the drug-loading microparticles made from solvent evaporation or adsorption using porous CaCO 3 microparticles to enhance the loading capacity and suppress the initial burst. Increasing the number of layers, raising the deposition temperature, and cross linking of the neighboring layers slowed down the enzymatic desorption of polyelectrolyte multilayer films and the releasing rate of encapsulated drug [75].…”
Section: Assembling Using Layer By Layer Techniquesmentioning
confidence: 99%
“…Even if such examples of LbL applications are still in some way sourced from petrochemistry, there can be no doubt that tailor-made bio-sourced packaging will soon be developed. This is especially the case considering recent interest in biomolecular architectures with protein assembly [3,43,51,79] and construction of clay-protein ultrathin films [49,57,76]. …”
Section: Improving/modulating Functional Propertiesmentioning
confidence: 99%